PENDEKATAN HOLISTIK DALAM PENDIDIKAN AGAMA ISLAM DI ERA DIGITAL - Masrizal, Masrizal (Hijri, 2021)
The digital era has brought significant changes to the education system, including Islamic religious education (PAI). Advances in information technology have opened up great opportunities to expand access, enrich learning methods, and deepen religious understanding. However, challenges such as moral degradation, unfiltered information flows, and changes in social interaction patterns require a comprehensive approach. This article discusses the concept of a holistic approach in Islamic religious education in the digital age, which integrates cognitive, affective, and psychomotor dimensions by leveraging technology wisely. This approach is expected to produce students who are not only intellectually intelligent but also spiritually mature, morally upright, and prepared to face global challenges.